Identification of the first plant caffeoyl-quinate esterases in Cichorium intybus - Mallavergne, Antoine; Mathiron, David; Molinié, Roland; Hilbert, Jean-Louis; Gagneul, David (Frontiers in Plant Science, 2025)
Chlorogenic acid (5-CQA) is a caffeic acid ester widely accumulated in higher plants. It plays roles in defense against biotic and abiotic stresses. As its biosynthetic pathway shares common enzymes and intermediates with that of lignin, 5-CQA has long been hypothesized to be involved in lignin formation. However, to date, no plant enzymes have been identified that efficiently convert 5-CQA into lignin precursors. While investigating enzymes involved in the conversion of 5-CQA to isochlorogenic acid (3,5-DiCQA) in chicory (Cichorium intybus), we identified two enzymes from the GDSL esterase/lipase family, CiCQE1 and CiCQE3. Biochemical characterization and functional analysis in tobacco revealed that both enzymes can hydrolyze 5-CQA and 3,5-DiCQA to release caffeic acid (CA) both in vitro and in planta. The genes encoding CiCQE1 and CiCQE3 are predominantly expressed in chicory roots, where 5-CQA and 3,5-DiCQA accumulate to high levels. When transiently expressed in tobacco leaves, accumulation of caffeoyl-putrescine in addition to CA was observed. This may suggest that released CA may be converted to caffeoyl-CoA to fuel other metabolic paths. The hydrolysis of caffeoyl-shikimate, a compound structurally close to 5-CQA, to caffeic acid, and its subsequent conversion to caffeoyl-CoA, has been shown to be an important step in the biosynthesis of G and S monolignols. Since CiCQE1 and CiCQE3 catalyze similar reactions using 5-CQA as substrate, these enzymes may represent a novel route for 5-CQA remobilization in chicory roots. Further functional characterization of the role of these genes using mutant lines is still required to fully understand their role in planta.